(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2021)
In this prospective study, we presented the effect of isokinetic training on the clinical outcome of rehabilitation in relation to the reduction of the torque deficit in thigh muscles (DEF) after anterior cruciate ligament (LCA) reconstruction. The prospective study followed 144 subjects, 72 women and 72 men, with a mean age of 28.20 ± 4.52, four months after anterior cruciate ligament reconstruction with a hamstring graft. Subjects were divided into two groups according to the type of rehabilitation treatment they underwent. Subjects of the isokinetic group (72 subjects, 36 males and 36 females), underwent kinesitherapy according to the isokinetic exercise protocol which consisted of a one-day isokinetic training lasting for thirty minutes, five times a week for six weeks. Subjects of the classical group (72 subjects, 36 males and 36 females) underwent kinesitherapy based on standard isotonic exercises to increase muscle strength, i.e. exercises with weights and in the gym. The difference in the outcome of rehabilitation was objectified by a concentric-concentric isokinetic test at an angular velocity of 60 °/s before the start, after three weeks and after six weeks of rehabilitation. The monitoring parameters were: torque deficit of the injured leg knee extensor in relation to the uninjured leg (EXDEF) -% and torque deficit of the knee flexor of the injured leg in relation to the uninjured leg (FLDEF) -%.